The master impersonator: Pulmonary tuberculosis mimicking diffuse cystic lung disease – A mini case series of a rare presentation - V Vinay; Yasir Abdullah; Abhimanyu Garg; Paras Verma; Gaurav Kumar Singh; Amit Sharma (Journal of Family Medicine and Primary Care, 2022)
Pulmonary tuberculosis has diverse clinical presentations. Cysts in the lung can arise due to large number of causes out of which tuberculosis is very rare. We report two immunocompetent cases of pulmonary tuberculosis who presented with multiple cysts in the lung parenchyma. The diagnosis was confirmed by the transbronchial lung cryobiopsy in first case and by analysis of bronchoalveolar lavage fluid in the second. Both had spontaneous pneumothorax which was treated with chest drain and pleurodesis. Both showed an excellent response to anti-tubercular therapy and steroids. Tuberculosis presenting as cystic lung disease is atypical and rare.